2016
DOI: 10.1089/jir.2015.0006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of EHMT2 Induces a Robust Antiviral Response Against Foot-and-Mouth Disease and Vesicular Stomatitis Virus Infections in Bovine Cells

Abstract: The genetic regulatory network controlling the innate immune system is well understood in many species. However, the role of the epigenetic mechanisms underlying the expression of immunoregulatory genes is less clear, especially in livestock species. Histone H3 lysine 9 dimethylation (H3K9me2) is an epigenetic modification associated with transcriptional silencing within the euchromatin regions. Euchromatic histone-lysine Nmethyltransferase 2 (EHMT2; also known as G9a) is a crucial enzyme responsible for regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
(9 reference statements)
1
10
0
Order By: Relevance
“…It has been reported that IFI44 is an IFN-inducible protein, related to infection of several viruses (Balan et al, 2006;Power et al, 2015;deDiego et al, 2019). Other studies documented that OAS1 plays an important role in antiviral activity as antiviral factor (Knapp et al, 2003;Melchjorsen et al, 2009;Singh et al, 2016). CASP1 participates in the composition of the inflammasome which actives the pro-inflammatory cytokines IL-18 and IL-1β, resulting in the proinflammatory cell death known as pyroptosis (Lupfer et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that IFI44 is an IFN-inducible protein, related to infection of several viruses (Balan et al, 2006;Power et al, 2015;deDiego et al, 2019). Other studies documented that OAS1 plays an important role in antiviral activity as antiviral factor (Knapp et al, 2003;Melchjorsen et al, 2009;Singh et al, 2016). CASP1 participates in the composition of the inflammasome which actives the pro-inflammatory cytokines IL-18 and IL-1β, resulting in the proinflammatory cell death known as pyroptosis (Lupfer et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The role of an enzyme involved in epigenetics modifications, the histone methyltransferase EHMT2, in regulation of bovine IFN-β gene expression and in the establishment of an antiviral state in primary bovine fibroblast cells has been reported, as well as the prophylactic and therapeutic use of EHMT2 inhibitors to control FMDV replication (Singh et al, 2016). …”
Section: Sensing Of Viral Genome and Induction Of Innate Responsesmentioning
confidence: 99%
“…Experiments in pigs showed a good correlation between IFN-induced protection against FMDV and induction of ISGs in skin, peripheral blood mononuclear cells, and lymphoid tissues (Diaz-San Segundo et al, 2010 ). The role of an enzyme involved in epigenetics modifications, the histone methyltransferase EHMT2, in regulation of bovine IFN-β gene expression and in the establishment of an antiviral state in primary bovine fibroblast cells has been reported, as well as the prophylactic and therapeutic use of EHMT2 inhibitors to control FMDV replication (Singh et al, 2016 ).…”
Section: Sensing Of Viral Genome and Induction Of Innate Responsesmentioning
confidence: 99%
“…Studies in porcine cells demonstrated that FMDV Lpro can promote its self-binding to the transcription factor activity-dependent neuroprotective protein (ADNP) and negatively regulate the activity of the IFN-α promoter ( 57 ). In contrast, chromatin changes that favor the upregulation of IFN and ISGs can inhibit FMDV replication ( 58 ). Interestingly, deletion or mutations in different domains of Lpro result in viral attenuation in vitro and in vivo ( 59 63 ).…”
Section: Foot-and-mouth Disease Virus Impairs Innate Immunity Moleculmentioning
confidence: 99%